Oral Administration of the Broad-Spectrum Antibiofilm Compound Toremifene Inhibits Candida albicans and Staphylococcus aureus Biofilm Formation In Vivo - De Cremer, Kaat (Antimicrob Agents Chemother, 2014)
We here report on the in vitro activity of toremifene to inhibit biofilm formation of different fungal and bacterial pathogens, including Candida albicans, Candida glabrata, Candida dubliniensis, Candida krusei, Pseudomonas aeruginosa, Staphylococcus aureus, and Staphylococcus epidermidis. We validated the in vivo efficacy of orally administered toremifene against C. albicans and S. aureus biofilm formation in a rat subcutaneous catheter model. Combined, our results demonstrate the potential of toremifene as a broad-spectrum oral antibiofilm compound.